Effect of add-on direct renin inhibitor aliskiren in patients with non-diabetes related chronic kidney disease - Li Szu-yuan; Chen Yung-Tai; Yang Wu-Chang; Tarng Der-Cherng; Lin Chih-Ching; Yang Chih-Yu; Liu Wen-Sheng (BMC Nephrology, 2012)
Abstract Background The renin-angiotensin-aldosterone system (RAAS) plays an important role in the progression of chronic kidney disease (CKD). Although dual RAAS inhibition results in worse renal outcomes than monotherapy in high risk type 2 diabetes patients, the effect of dual RAAS inhibition in patients with non-DM CKD is unclear. The aim of this study was to evaluate the potential renoprotective effect of add-on direct renin inhibitor in non-DM CKD patients. Methods We retrospectively enrolled 189 non-DM CKD patients who had been taking angiotensin II receptor blockers (ARBs) for more than six months. Patients were divided into an add-on aliskiren group and an ARB monotherapy group. The primary outcomes were a decline in glomerular filtration rate (GFR) and a reduction in urinary protein-to-creatinine ratio at six months. Results The baseline characteristics of the two groups were similar. Aliskiren 150 mg daily reduced the urinary protein-to-creatinine ratio by 26% (95% confidence interval, 15 to 37%; p < 0.001). The decline in GFR was smaller in the add-on aliskiren group (−2.1 vs. -4.0 ml/min, p = 0.038). Add-on aliskiren had a neutral effect on serum potassium in the non-DM CKD patients. In subgroup analysis, the proteinuria-reducing effect of aliskiren was more prominent in patients with a GFR less than 60 ml/min, and in patients with a urinary protein-to-creatinine ratio greater than 1.8. The effect of aliskiren in retarding the decline in GFR was more prominent in patients with hypertensive nephropathy than in those with glomerulonephritis. Conclusion Add-on direct renin inhibitor aliskiren (150 mg daily) safely reduced proteinuria and attenuated the decline in GFR in the non-DM CKD patients who were receiving ARBs.